Rebaseline no evidence of disease activity (NEDA-3) as a predictor of long-term disease course in a Norwegian multiple sclerosis population - Simonsen, Cecilia Smith; Flemmen, Heidi Øyen; Broch, Line; Brekke, Kamilla; Brunborg, Cathrine; Berg-Hansen, Pål; Celius, Elisabeth Gulowsen (Frontiers in Neurology, 2022)
Introduction: No evidence of disease activity with three components (NEDA-3) is achieved if the person with MS (pwMS) has no new MRI lesions, no new relapses and no change in Expanded disability status scale (EDSS) over one year. Whether NEDA-3 is a good tool in measuring disease activity and long-term disability is up for discussion. Methods: Retrospective cohort study using real-world data from the complete MS population at two hospitals in the southeast of Norway. We included pwMS diagnosed between 2006 and 2017 who had enough information to determine time to failure of NEDA-3 after diagnosis. Results: Of 536 pwMS, only 38% achieved NEDA one year after diagnosis. Time to NEDA failure was 3.3 (95% CI 2.9-3.7) years. PwMS who achieved NEDA at year one had a time to EDSS 6 of 33.8 (95% CI 30.9-36.8) years vs 30.8 (95% CI 25.0-36.6) years in pwMS who did not achieve NEDA, p<0.001. Starting a high efficiacy therapy was associated with an increased risk of sustaining NEDA as compared to moderate efficacy therapy. When rebaselining NEDA one year after diagnosis, 52.2% achieved NEDA, time to NEDA failure was 3.4 (95% CI 3.0-3.7) years and time to EDSS 6 was 44.5 (95% CI 40.4-48.5) years in pwMS achieving NEDA versus 29.6 (95% CI 24.2-35.0) years in pwMS not achieving NEDA, p<0.001. After rebaseline, pwMS on high efficacy therapy as the initial drug had a time to NEDA fail of 4.8 years (95% CI 3.9-5.8) vs 3.1 years (95% CI 2.7-3.5) in pwMS started on a moderate efficacy therapy, p<0.001. In pwMS with NEDA failure at year one, 70% failed one components. New MRI lesions were the most common cause of NEDA failure. Conclusions: NEDA-3 from rebaseline after one year, once treatment is stabilised, can predict the long-term disease course in MS. Starting a high efficacy DMT is associated with longer time to NEDA failure than moderate therapies. Finally, most pwMS only fail one component and new MRI lesions are the most likely cause of NEDA failure.